(untitled) (Journal of Engineering, 2012)
This paper reports an experimental study regarding the influence of vertical oscillations on the natural convection heat transfer from a vertical channel. An experimental set-up was constructed and calibrated; the vertical channel was tested in atmosphere at 25o C. The channel-to-ambient temperature difference was varied with the power supply to the electrical heater ranging between 15W to 70W divided into five levels. Data sets were measured under different operating condition from a test rig under six vibrating velocities (VVs) levels ranging from (5-30 m/s) in addition to the stationary state. The results show that the maximum heat transfer enhancement factor (E) occurs at Rayleigh number (Ra=2.328×103 ) and vibrational Reynolds number ( Rev=6.365×103 ); this enhancement reached to (7.685%).The results also illustrated that the temperature gradient along the channel wall length was enhanced by inducing the oscillatory motion to the channel. Rayleigh and vibrational Reynolds numbers were ranging between (2.306×103 - 5.564×103) and (0.0 - 19.86×103) respectively. Finally, A correlation which summarized the effects of both Ra and Rev was determined for the Nusselt numbers.